An annotated checklist of pathogenic microorganisms associated with migratory birds - Hubálek, Zdenek (Journal of wildlife diseases, 2004)
The potential for transport and dissemination of certain pathogenic microorganisms by migratory birds is of concern. Migratory birds might be involved in dispersal of microorganisms as their biological carriers, mechanical carriers, or as carriers of infected hematophagous ecto-parasites (e.g., ixodid ticks). Many species of microorganisms pathogenic to homeothermic vertebrates including humans have been associated with free-living migratory birds. Migratory birds of diverse species can play significant roles in the ecology and circulation of some arboviruses (e.g., eastern and western equine encephalomyelitis and Sindbis alphaviruses, West Nile and St. Louis encephalitis flaviviruses), influenza A virus, Newcastle disease virus, duck plague herpes-virus, Chlamydophila psittaci, Anaplasma phagocytophilum, Borrelia burgdorferi sensu lato, Campylobacter jejuni, Salmonella enterica, Pasteurella multocida, Mycobacterium avium, Candida spp., and avian hematozoans. The efficiency of dispersal of pathogenic microorganisms depends on a wide variety of biotic and abiotic factors affecting the survival of the agent in, or disappearance from, a habitat or ecosystem in a new geographic area.
Keywords: Bird Diseases; Parasitic Diseases, Animal; migrace zvířat; nemoci ptáků; Animals, Wild; bakteriální infekce; ptáci; divoká zvířata; Animals; Bacterial Infections; Birds; Disease Reservoirs; Virus Diseases; zdroje nemoci; parazitární nemoci u zvířat; zvířata; Animal Migration; virové nemoci